An evaluation of staff experiences of the Royal Literary Fund writer-in-residence service to support improvements in written communication in healthcare - Catherine Pengelly; Carolyn Spring; Rachel M. Taylor (Qualitative Research in Medicine & Healthcare, 2023)
Written communication is essential to staff and patient experience in healthcare. The Royal Literary Fund has hosted a writing fellow in an NHS Trust since 2018 providing professional writing training. The aim of this evaluation was to explore the experiences of staff using the service. Semi-structured interviews were conducted with 21 staff members from a range of professions who had accessed the service. Data were analysed using thematic analysis. Findings: The writing service was highly valued. Three themes emerged: feelings about writing at work, reported benefits of attending sessions, and perceived barriers to accessing them. Staff felt underskilled in professional writing and described the wish to write more succinctly and reflectively. Self-reported confidence increased after sessions. Stigma around writing skills prevented some staff from recommending the service. Wider adoption of professional writing skills training through the NHS could have benefits in terms of increasing self-perceived skills and confidence.